ANALISIS ALIH KODE DAN CAMPUR KODE DALAM RAPAT MENGANANALISA KENDALA LAPANGAN DI AUTO 2000 MANGGA DUA JAKARTA PUSAT - Dini Nursukma Andrini (IKIP Siliwangi, 2020)
The problems raised in this study is code switching and code mixing in meetings to analysis field constraints in Auto 2000 Mangga Dua. The aim is to describe the existence of code switching in the form of words, phrases, clauses, sentences and causative factors in the language that used by members of the meeting. The source of data that used in the study is meeting members at Auto 2000 Mangga Dua. The data taken base on the form of oral speech from the members during the meeting. The method used descriptive qualitative method, the data collected through observation techniques, video recordings and interviews to determine the causative factors. The results showed that in the language that used by meeting members at Auto 2000 during the meeting, there were (1) Code Switching in the form of phrases, clauses, and sentences (2) Code Mixing in the form of phrases, clauses and words. The contributed factor is to break the ice so that the participants do not feel tense during the meeting.